Analisa Kinerja Multiple Input Multiple Output Jaringan Sensor Nirkabel dengan Demodulasi Terdistribusi - Ari Endang Jayati; Sri Heranurweni; M. Sipan (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
Wireless Sensor Network has some weaknesses, such as limited power, memory and communication. Sensor is supplied with a very limited power batery. Besides, Wireless Sensor Network should also consider the available bandwidth, range sensor and sensor communication range. The main objective of this study is to analyze the performance of linear demodulation named Zero Forcing (ZF) and Minimum Mean Squared Error (MMSE) in wireless sensor network using Multiple Input and Multiple Output (MIMO) system with Signal to Noise Ratio (SNR) and Bit Error Rate (BER) as the parameter to measure the performance of endurance to noise. The application of ZF and MMSE linear demodulation with MIMO configuration to Wireless Sensor Network is constantly good, the performance of ZF to reach BER 10-3 needed SNR 21 dB, while the performance of MMSE to reach BER 10-3 needed SNR 18 dB.